Exploring the Potential of Composting for Bioremediation of Pesticides in Agricultural Sector - Lau, Yu Yan; Hernandes, Erika; Kristanti, Risky Ayu; Wijayanti, Yureana; Emre, Mehmet (Tecno Scientifica Publishing, 2023)
The rapid expansion of the human population has raised the chemical stress on the environment due to the increased demand of agricultural yields. The use of pesticides is the primary contributor to environmental chemical stress, which is essential for agricultural expansion in order to produce enough food to sustain the burgeoning human population. Pesticide residues in soil have grown to be a subject of rising concern as a result of their high soil retention and potential harm to unintended species. Diverse remediation strategies, such as physical, chemical, and biological, for limiting and getting rid of such contaminants have been put forth to deal with this problem. Bioremediation is one of these techniques, which has been deemed the best for reducing pollution because of its low environmental impact, simplicity of operation and construction. Microorganisms are implemented in this technique to break down and get rid of toxins in the environment or to reduce the toxicity of chemical compounds. This study thoroughly analyses the different composting soil remediation methods, including landfarming, biopiles, and windrows, to reduce and eliminate soil pollution. Although biological treatment is the best option for cleaning up polluted soil, it is still important to evaluate and review the approaches over the long term to determine whether they are effective in the field. It is because the reactivity of the microorganisms is highly dependent on environmental parameters, and the contemporary environment is characterised by unpredictable weather patterns, localised droughts, and temperature fluctuations.